2016
DOI: 10.1007/s10709-016-9935-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity in an isolated population of an endemic mole salamander (Ambystoma rivulare Taylor, 1940) of central Mexico

Abstract: Human activities are affecting the distribution of species worldwide by causing fragmentation and isolation of populations. Isolation and fragmentation lead to populations with lower genetic variability and an increased chance of inbreeding and genetic drift, which results in a loss of biological fitness over time. Studies of the genetic structure of small and isolated populations are critically important for management and conservation decisions. Ambystoma rivulare is a micro-endemic Mexican mole salamander f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 84 publications
(89 reference statements)
0
7
0
6
Order By: Relevance
“…The observed heterozygosity values were high and most of thegenotypes were heterozygous (table 2; table 2 in electronic supplementary material); high levels of genetic variability are not unusual in Ambystoma species (Goprenko et al 2007;Greenwald et al 2009;Sunny et al 2014a;Heredia-Bobadilla et al 2016;Percino-Daniel et al 2016), despite with a limited distribution. The genetic variability found in this study was higher than that reported for A. altamirani from the Lagunas de Zempoala National Park (LZNP) (Parra-Olea et al 2012), this may be due to the high anthropogenic pressures occurring in the LZNP, of the seven lagoons that inhabited A. altamirani, three are already completely dried and in the four other lagoons, the aquatic vegetation is disappearing and pollution is increasing and the deforestation and ecotourism activities are devastating the ecosystem (Islebe et al 2003;Lemos-Espinal 2003;Parra-Olea et al 2012).…”
Section: Genetic Variabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…The observed heterozygosity values were high and most of thegenotypes were heterozygous (table 2; table 2 in electronic supplementary material); high levels of genetic variability are not unusual in Ambystoma species (Goprenko et al 2007;Greenwald et al 2009;Sunny et al 2014a;Heredia-Bobadilla et al 2016;Percino-Daniel et al 2016), despite with a limited distribution. The genetic variability found in this study was higher than that reported for A. altamirani from the Lagunas de Zempoala National Park (LZNP) (Parra-Olea et al 2012), this may be due to the high anthropogenic pressures occurring in the LZNP, of the seven lagoons that inhabited A. altamirani, three are already completely dried and in the four other lagoons, the aquatic vegetation is disappearing and pollution is increasing and the deforestation and ecotourism activities are devastating the ecosystem (Islebe et al 2003;Lemos-Espinal 2003;Parra-Olea et al 2012).…”
Section: Genetic Variabilitymentioning
confidence: 94%
“…We found low, but significant levels of gene flow (N m = 1.74 means that in five generations, there are ≈8−9 migrants), this also explains the low genetic differentiation (F ST = 0.005). There are some characteristics of the biology of the mole salamander that favours the low gene flow and also the genetic structure, like the philopatric tendencies and low vagility (Funk et al 2005;Savage and Zamudio 2005;Spear et al 2005;Gamble et al 2007;Vences and Wake 2007;Calhoun and deMaynadier 2008;Semlitsch 2008;Wang et al 2009;Wang and Summers 2010;Parra-Olea et al 2012;Sunny et al 2014a;Sunny et al 2014b;Heredia-Bobadilla et al 2016;Percino-Daniel et al 2016). During the six months of sampling, we found the same individuals in the same pond, which reflects few migratory movements; although, this species can undergo metamorphosis, A. altamirani prefers to stay in the water (Lemos-Espinal et al 1999;Shaffer et al 2008), thus, it is unlikely that A. altamirani can be dispersed by land in this locality.…”
Section: Gene Flow Effective Population Size Bottlenecks and Relatementioning
confidence: 99%
“…En Michoacán habita en los municipios de Zitácuaro y Angangueo, que forman parte de la Reserva de la Biósfera de la Mariposa Monarca (RBMM), ubicada entre los estados de Michoacán y México, con una extensión de 56,259 ha dentro de las cuales se encuentran al menos ocho asentamientos humanos. En el Estado de México su distribución es más amplia, existen poblaciones en los municipios de Villa de Allende, Villa Victoria, Toluca, Zinacantepec, Temascaltepec y Calimaya, estos últimos cuatro forman parte del Área de Protección de Flora y Fauna Nevado de Toluca (APFFNT), donde esta especie tiene mayor número de poblaciones, al menos 12, distribuidas en las 54,000 ha que forman el área natural protegida (Barriga-Vallejo et al, 2015;Lemos-Espinal et al, 2015;Heredia-Bobadilla et al, 2016;Monroy-Vilchis et al, 2019).…”
Section: Método De Evaluación De Riesgo De Extinción De Especies Silvestresunclassified
“…Pinus forests of the FFPANT are home and a potential distribution area of many species of plants and animals some of which also have high levels of genetic variability which in turn makes FFPANT an important place to conservation of species [4,[57][58][59][60]. These forests provide water to urban areas, hence the importance of preserving this natural area should not be dismissed; there is an urgent need to protect these forests, as long as forest fragmentation is increasing.…”
Section: Conservation Implicationsmentioning
confidence: 99%